Ecophysiology of egg rejection in hosts of avian brood parasites: new insights and perspectives. Issue 6 (12th May 2021) - Ruiz-Raya, Francisco
Abstract: Egg rejection is the most effective and widespread defense used by host species to counteract the extreme fitness costs frequently imposed by obligate avian brood parasites. Yet, the proximate mechanisms underlying between- and within-individual variation in host responses remain poorly explored. Emerging evidence suggests that egg rejection is dependent on individual physiological states, and draws attention to the role of hormones as mediators of flexible antiparasitic responses. In this perspective article, I outline recent advances in our understanding of the proximate factors that mediate egg rejection. I also point out some areas where knowledge remains still lacking, especially those related to the development and maintenance of effective cognitive functions, the potential role of oxidative stress, immunological state, and developmental stressors. I propose new hypotheses that stimulate future research on behavioral host responses toward brood parasitism.